The Role of Family Environment in Social Networking Sites Addiction among University Students - Bani-Hamad, Abeer O.; Jaradat , Abdul-Kareem M. (Dirasat: Educational Sciences, 2022)
Objectives: This study aimed to explore the differences in family environment of students who are addicted to social networking sites, and those who are not. Additionally, the study aimed to investigate the contribution of family environment to Social Networking Sites Addiction (SNSA) among Jordanian university students. Methods: The sample of the study consisted of 629 undergraduate students. Data were collected online, using two scales for measuring family environment and SNSA. The study utilized the descriptive-predictive method by distributing a questionnaire to the study participants via google forms. Results: Results revealed significant differences in the mean scores of students addicted to social networking sites, and those who were not on the subscales of the family environment scale, where students who were not addicted scored higher on the subscales of cohesion, expressiveness and organization, whereas addicted students scored higher on the conflict subscale. It was found that the dimensions of conflict, intellectual-cultural orientation and expressiveness of the family environment scale predicted SNSA in males; and the dimensions of conflict and expressiveness predicted SNSA in females. Conclusions: The level of addiction to social networking sites among university students is determined according to the family environment in which they live. If the family environment is characterized by cohesion and gives children freedom of expression and encourages organization, then the children will not resort to social networking sites as a means to escape from the conditions in which they live; and on the contrary if the environment is dominated by ongoing conflicts between family members.